ONLINE LEARNING CLASSROOM MANAGEMENT DURING THE COVID-19 PERIOD AT PGMI IAIN BATUSANGKAR - Yufi Latmini Lasari (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2021)
This research is motivated by the Covid-19 pandemic. In mid-March 2020, the face-to-face lecture process between lecturers and students can no longer be carried out normally as usual. To respond to this, the lecturers of PGMI IAIN Batusangkar carry out online lecture activities. Based on these facts, this research was conducted with the aim of describing the forms of classroom management carried out by lecturers in online learning during the Covid-19 period at PGMI IAIN Batusangkar. The research method used in this research is descriptive qualitative method. The results illustrate that there are several stages carried out by researchers in managing online learning classes at PGMI IAIN Batusangkar, namely: 1) the planning stage, 2) the implementation stage, and 3) the control stage. Keywords: Class Management, Online Learning, Covid-19 Period. Abstrak Penelitian ini dilatarbelakangi oleh pandemi Covid-19. Pada pertengahan Maret 2020, proses perkuliahan tatap muka antara dosen dan mahasiswa sudah tidak bisa lagi berjalan normal seperti biasanya. Menyikapi hal tersebut, para dosen PGMI IAIN Batusangkar melaksanakan kegiatan kuliah online. Berdasarkan fakta tersebut maka penelitian ini dilakukan dengan tujuan untuk mendeskripsikan bentuk-bentuk pengelolaan kelas yang dilakukan oleh dosen dalam pembelajaran online selama periode Covid-19 di PGMI IAIN Batusangkar. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Hasil penelitian menggambarkan bahwa ada beberapa tahapan yang dilakukan peneliti dalam mengelola kelas pembelajaran online di PGMI IAIN Batusangkar, yaitu: 1) tahap perencanaan, 2) tahap pelaksanaan, dan 3) tahap pengendalian.